Pengaruh Metode Complex Training Terhadap Peningkatan Power Tungkai Atlet Futsal Putra Kota Bandung - Muhammad Fakhriansyah; Fitri Rosdiana; Rizky Indra Cahyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effect of complex training on lower-limb power in male futsal athletes in Bandung City. A pre-experimental method with a one-group pretest-posttest design was employed, involving 15 male futsal athletes selected through total sampling and given a six-week complex training program performed 2–3 times per week; lower-limb power was assessed using the Triple Hop Jump Test and analyzed using the Wilcoxon Signed Rank Test. The results showed an average increase in lower-limb power of 7.41% in the left leg (from 6.696 m to 7.192 m) and 10.99% in the right leg (from 6.578 m to 7.301 m), with significance values of 0.007 (left leg) and 0.002 (right leg), both below 0.05. It can be concluded that complex training significantly affects the improvement of lower-limb power in futsal athletes, making it a viable alternative training program for coaches. Keywords: Complex Training, Futsal, Plyometric, Lower-Limb Power, Triple Hop Jump Test